Evaluation of the Antioxidant and Hepatoprotective Activity of Cryptolepis Buchanani - K. Padmalochana & , M.S. Dhana Rajan, R.Lalitha, H.Sivasankari (Journal of Applied Pharmaceutical Science, 2013)
Cryptolepis buchanani (Berberidaceae) is a climbing tree, leaves is widely used in folk medicine in Southeast Asia. The alcoholic extract of stem of this plant is commonly used for the treatment of inflammatory conditions such as arthritis, and muscle and joint pain. The development of hepatotoxicity induced by acetaminophen is promoted by oxidative stress. The aim of the present study was to investigate the hepatoprotective effect and antioxidant activities of the ethanolic extract of Cryptolepis buchanani on acetaminophen induced hepatotoxicity in rats. We observed that the ethanolic extract of cryptolepis buchanani conferred hepatoprotectivity. Biochemical observations confirmed the beneficial roles of Cryptolepis buchanani and silymarin against acetaminophen induced liver injury in rats.
Keywords: Hepatoprotective, Cryptolepis buchanani,&lt